2002
DOI: 10.1002/ps.506
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide loss following application to a roadside

Abstract: Risk assessments for herbicides applied to roads are limited by the lack of knowledge on the fate and behaviour of the compounds in the urban environment. This study was designed to address this deficiency by quantifying the percentage loss of six herbicides following application to a roadside. Herbicides were applied on two occasions to a 16-m length of roadside and kerb edge. An automatic water sampler was used to collect run-off, draining to a single gulley pot, until 25 mm of rain had fallen. Samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 2 publications
4
27
0
1
Order By: Relevance
“…Glyphosate residue contamination has been demonstrated to correlate with sources of agricultural applications (Payne, 1992;Coupe et al, 2012) corresponding to GM crop cultivation (Barceló and Hennion, 1997;Skark et al, 1998;Australian Academy of Technological Sciences, and Engineering, 2002;Ramwell et al, 2002;Peruzzo et al, 2008;Aparicio et al, 2013;Davis et al, 2013;Mardiana-Jansar and Ismail, 2014;Lupi et al, 2015;Ronco et al, 2016;Caprile et al, 2017;, post-harvest chemical desiccation (Shipitalo and Owens, 2011;Soracco et al, 2018) or other technologies in intensive agriculture e.g., biomass production of industrial crops (Mardiana-Jansar and Ismail, 2014). Moreover, non-agricultural or urban uses of FIGURE 4 | Maximal residue levels (µg/l) of glyphosate (black) and AMPA (gray in parentheses) in surface and ground water reported worldwide.…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…Glyphosate residue contamination has been demonstrated to correlate with sources of agricultural applications (Payne, 1992;Coupe et al, 2012) corresponding to GM crop cultivation (Barceló and Hennion, 1997;Skark et al, 1998;Australian Academy of Technological Sciences, and Engineering, 2002;Ramwell et al, 2002;Peruzzo et al, 2008;Aparicio et al, 2013;Davis et al, 2013;Mardiana-Jansar and Ismail, 2014;Lupi et al, 2015;Ronco et al, 2016;Caprile et al, 2017;, post-harvest chemical desiccation (Shipitalo and Owens, 2011;Soracco et al, 2018) or other technologies in intensive agriculture e.g., biomass production of industrial crops (Mardiana-Jansar and Ismail, 2014). Moreover, non-agricultural or urban uses of FIGURE 4 | Maximal residue levels (µg/l) of glyphosate (black) and AMPA (gray in parentheses) in surface and ground water reported worldwide.…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…For instance, impervious surfaces comprise 25 to 60% of surfaces in a typical medium-density, singlefamily home residential area [13]. Urban hardscapes have low infiltration rates and are designed to facilitate surface runoff that may contain pollutants [11,[14][15][16]. Pesticides may be applied directly to concrete or similar hard surfaces, such as in treatments for ant trail eradication.…”
Section: Introductionmentioning
confidence: 99%
“…Piccolo et al 21 suggested that adsorption of glyphosate to humic substances was just as important as adsorption to clay minerals, while Gerritse et al 6 found that organic matter reduced the adsorption of glyphosate in sandy soils. Despite relatively strong sorption in soils, mobility of both glyphosate and its primary metabolite, aminomethyl‐phosphonic acid (AMPA), has been demonstrated in clay soil,22 in gravel23 and on asphalt surfaces 24. Few studies have hitherto addressed the behaviour of glyphosate in gravel 23, 24.…”
Section: Introductionmentioning
confidence: 99%